2019
DOI: 10.1111/ger.12414
|View full text |Cite
|
Sign up to set email alerts
|

The residual dentition among New Zealanders in aged residential care

Abstract: Background Descriptions of the older population's dentition status are usually limited to indicators such as the edentulous proportion, the mean number of restored and missing teeth, and the proportion with a functional dentition, with very few reports describing in detail the nature of the residual dentition. Objectives This study described the residual dentition among older New Zealanders living in residential aged care facilities. Material and Methods Using national data from the Older People's Oral Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…The team leaders need to supervise the work of primary nurses to correct deficiencies. For the department leaders, they should supervise the daily work of primary nursing, conduct a check-up system to comprehensively grasp the causes of clinical adverse events, analyze the risk factors affecting the quality of care, and fundamentally ensure the smooth development of nursing services [ 18 , 20 , 21 ]. This study showed that the incidence of clinical adverse events in the research group was significantly lower than that in the reference group, suggesting that the combined nursing intervention can effectively improve the responsibility consciousness of nursing staff and reduce the incidence of clinical adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The team leaders need to supervise the work of primary nurses to correct deficiencies. For the department leaders, they should supervise the daily work of primary nursing, conduct a check-up system to comprehensively grasp the causes of clinical adverse events, analyze the risk factors affecting the quality of care, and fundamentally ensure the smooth development of nursing services [ 18 , 20 , 21 ]. This study showed that the incidence of clinical adverse events in the research group was significantly lower than that in the reference group, suggesting that the combined nursing intervention can effectively improve the responsibility consciousness of nursing staff and reduce the incidence of clinical adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Thomson et al 6 . (2018) and Hyland et al 5 . (2019) suggested that the dental caries and treatment needs were very high, even though there is a decline in edentulism.…”
Section: Introductionmentioning
confidence: 99%
“…A recent national survey 5 conducted among 987 elderly residents in 120 residential homes in New Zealand suggested that almost 45% (n = 443) of participants (65+) were dentate. The studies by Thomson et al 6 (2018) and Hyland et al 5 (2019) suggested that the dental caries and treatment needs were very high, even though there is a decline in edentulism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations